Предмет: Математика,
автор: m672
x = 8 - sqrt(60)
найти sqrt(x) - sqrt(3)
Ответы
Автор ответа:
1
x = 8 - sqrt(60) = 8 - 2*sqrt(15) = 5 - 2*sqrt(3)*sqrt(5) + 3 = (sqrt(5) - sqrt(3))^2
sqrt(x) - sqrt(3) = sqrt(5) - sqrt(3) - sqrt(3) = sqrt(5) - 2*sqrt(3)
sqrt(x) - sqrt(3) = sqrt(5) - sqrt(3) - sqrt(3) = sqrt(5) - 2*sqrt(3)
Похожие вопросы
Предмет: Другие предметы,
автор: Кот007004
Предмет: Английский язык,
автор: mwki
Предмет: Русский язык,
автор: Настя10331
Предмет: Математика,
автор: riemmamuravyova
Предмет: География,
автор: mamedovadinara2003